2022
DOI: 10.1186/s12998-022-00412-w
|View full text |Cite
|
Sign up to set email alerts
|

Intervention usage for the management of low back pain in a chiropractic teaching clinic

Abstract: Background Despite numerous low back pain (LBP) clinical practice guidelines, published studies suggest guideline nonconcordant care is still offered. However, there is limited literature evaluating the degree to which chiropractors, particularly students, follow clinical practice guidelines when managing LBP. The aim of this study was to evaluate the frequency of use of specific interventions for LBP by students at a chiropractic teaching clinic, mapping recommended, not recommend, and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Another study shows that Danish PTs often informed about the benign nature of LBP but were hesitant to advise on return to normal activity and work, while they provided advice on posture and ergonomics which is not recommended 26. This example, along with several others,16 27 illustrates the eclectic composition of recommended and non-recommended care across primary care.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study shows that Danish PTs often informed about the benign nature of LBP but were hesitant to advise on return to normal activity and work, while they provided advice on posture and ergonomics which is not recommended 26. This example, along with several others,16 27 illustrates the eclectic composition of recommended and non-recommended care across primary care.…”
Section: Discussionmentioning
confidence: 98%
“…A Canadian study of a chiropractic teaching clinic showed that most treatment plans for LBP patients included guideline-concordant care (eg, patient education, exercise and spinal manipulation/mobilisation) but also often non-recommended care like manual therapy as monotherapy. 16 This monodisciplinary example indicates that both recommended and non-recommended elements of care may be provided concomitantly. Still, it does not provide insights into the most frequent combinations of care offered to patients with LBP or whether the findings are generalisable to other primary healthcare provider groups that care for LBP patients.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the likelihood of attending a given profession may have been driven by the availability of each type of profession. For example, in the last year of the * p < 0.01 1 Odds ratio (99% confidence interval) 2 Reference category 3 Cells suppressed 4 Cells perturbed at random to suppress small cell sizes 5 Regional and remote are combined in descriptive statistics due to small cell sizes study ( 2015), Victoria had 17.4 osteopaths per 100,000 residents, compared to 3.8 per 100,000 in Queensland, and 2.1 and 2.4 in South Australia and Western Australia, respectively [34]. The differences in rates of clinicians aligns with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many health professionals including physiotherapists, chiropractors, and osteopaths can provide many of the recommended treatments for low back pain [3,4]. However, the more specific therapeutic choices and modes of delivery may vary by clinician training and profession-specific guidelines [5][6][7][8], and these may be supported by varying levels of evidence [7,9]. Workers' compensation schemes fund reasonable and necessary health care and rehabilitation services for individuals who are unable to work due to work-related conditions, including low back pain [10,11].…”
Section: Introductionmentioning
confidence: 99%